2015
DOI: 10.1039/c4ay02598a
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of two morphologically similar Amazonian Aniba species by mass spectrometry leaf fingerprinting

Abstract: Leaves from the morphologically similar Aniba rosaeodora and Aniba parviflora were used to obtain ESI and VL-EASI-MS fingerprinting spectra. The method differentiated rapidly and unequivocally the two species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 39 publications
(25 reference statements)
0
15
0
Order By: Relevance
“…In negative mode, this compound presented 3 pseudomolecular ions [M+Cl] − at m/z 487 and 489, [M+COOH] − at m/z 497. The compound showed characteristic MS 2 fragments of (epi)catechin (Galaverna, Sampaio, Barata, Eberlin, & Fidelis, ; Kang, Price, Ashton, Tapsell, & Johnson, ), so it was tentatively identified as (+)‐(epi)catechin‐ O ‐hexoside.…”
Section: Resultsmentioning
confidence: 99%
“…In negative mode, this compound presented 3 pseudomolecular ions [M+Cl] − at m/z 487 and 489, [M+COOH] − at m/z 497. The compound showed characteristic MS 2 fragments of (epi)catechin (Galaverna, Sampaio, Barata, Eberlin, & Fidelis, ; Kang, Price, Ashton, Tapsell, & Johnson, ), so it was tentatively identified as (+)‐(epi)catechin‐ O ‐hexoside.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the culture establishment procedure on samples of S. pulcherrimum twenty-seven compounds, listed in Table S8, were used as markers. Of this total, fourteen were identified as tannins through data compared with those described in the literature [63,67] or with spectra libraries (GNPS, METLIN, and HMDB). After comparing the samples in natura with the samples collected at each step of the in vitro culture establishment procedure of S. pulcherrimum on the LC-MS directed metabolic study, significant changes were observed.…”
Section: Stryphnodendron Pulcherrimum (Willd) Hochrmentioning
confidence: 99%
“…Among the few studies on Pará state samples, A. rosiodora from Emílio Goeldi Museum campus (city of Belém), the flavonoid pinocembrin was the major compound identified in the leaves, using mass spectra [ 9 ]. Analysis of seedling’s leaves from A. rosiodora collected in the Ducke Forest Reserve (Manaus, Amazonas) indicated the benzophenones cotoin and hydroxycotoin as key compounds for these seedlings [ 11 ]. Cotoin is found in high amounts in the A. rosiodora woods [ 24 ], but is not common in leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Due to extreme difficulties in distinguishing specimens based on morphology [ 7 ], it is not known whether the phytochemical variants align with the taxonomic varieties. The majority of the studies focused on the chemical and genetic variability in plants from the Amazon State [ 11 , 12 ]. As a further complication, rosewood is frequently misidentified as other species, such as Aniba parviflora (Meisn.)…”
Section: Introductionmentioning
confidence: 99%